Pengaruh Person Job Fit Dan Person Organization Fit Terhadap Kinerja Pegawai Perumda Air Minum Wair Pu’an Kabupaten Sikka - Fransiska Aprilia; Imanuel Wellem; Yosef Tonce (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
The background of this research was that the employees' performance at Wair Pu'an Municipal Waterworks of Sikka Regency had not been maximized. This research aimed to: (1) determine the description of employee performance, person-job fit, and person-organization fit; and (2) analyze the effect of person-job fit and person-organization fit on employee performance both partially and simultaneously. The population in this research were employees at Wair Pu'an Municipal Waterworks of Sikka Regency as many as 50 people. This research was conducted by census or saturated sampling due to limited population. Data were collected through questionnaires and analyzed through descriptive and inferential statistical methods, namely multiple linear regression. Hypothesis testing was done through the F-test and t-test. The results of descriptive analysis showed that the variable of employee performance. person-job fit, and person-organization fit were categorized as good. The results of the t-test statistic indicated that partially the person-job fit and person-organization fit variables had a positive and significant effect on employee performance. The results of the F-test statistic showed that simultaneously the person-job fit and person-organization fit variables significantly affected employee performance. The results of the determination analysis showed that the two independent variables in this research were able to explain the fluctuation of employee performance at Wair Pu'an Municipal Waterworks of Sikka Regency by 42.1%.